A model of equatorial and low latitude VHF scintillation in India - Iyer, K.N.; Souza, J.R.; Pathan, B.M.; Jivani, M.N.; Joshi, H.P.; Abdu, M.A. (My University, 2006)
Using the observed VHF scintillations at equatorial and anomaly crest stations in India during the years 1987-1989, an empirical model is developed. The model employs the cubic spline technique to reproduce the variation of scintillation occurrence with local time, season, solar activity and latitude. The modelled values are compared with observed ones and the agreement is found to be quite good.
Keywords: Ionospheric scintillations; Cubic spline technique; VHF scintillations; Scintillations